Male and female are not the same: a multicenter study of static and dynamic functional connectivity in relapse-remitting multiple sclerosis in China - Wang, Yao; Duan, Yunyun; Wu, Yuling; Zhuo, Zhizheng; Zhang, Ningnannan; Han, Xuemei; Zeng, Chun; Chen, Xiaoya; Huang, Muhua; Zhu, Yanyan; Li, Haiqing; Cao, Guanmei; et al. (Frontiers in Immunology, 2023)
Background: Sex effects have been observed in relapsing-remitting multiple sclerosis (RRMS), but its effects on functional network remain unclear.Objective: To investigate sex-related differences in connectivity strength and time variability within large-scale networks in RRMS.Methods: This is a multi-center retrospective study. A total of 208 RRMS (135 females; 37.55±11.47 years old) and 228 healthy controls (123 females; 36.94±12.17 years old) were included. All participants underwent clinical and MRI assessments.Independent component analysis was used to extract resting-state networks (RSNs).We assessed the connectivity strength using spatial maps (SMs) and static functional network connectivity (sFNC), and dynamic functional network connectivity (dFNC) was preformed to evaluate temporal properties and dFNC pattern of RSNs, and investigated their associations with structural damage or clinical variables.Results: For static connectivity, only male RRMS patients displayed decreased SMs in the attention network and reduced sFNC between the sensorimotor network and visual or frontoparietal networks compared with healthy controls [P<0.05, false discovery rate (FDR) corrected]. For dynamic connectivity, three recurring states were identified for all participants: State 1 (sparse connected state; 42%), State 2 (middle-high connected state; 36%), and State 3 (high connected state; 16%). dFNC analyses suggested that altered temporal properties and dFNC pattern only occurred in females: female patients showed higher fractional time (P<0.001) and more dwell time in State 1 (P<0.001) with higher transitions (P=0.004) compared to healthy females; Receiver operating characteristic curves revealed that fraction time and mean dwell time of State 1 could significantly distinguish female patients from controls (area under the curve: 0.838-0.896). In addition, female patients with RRMS also mainly showed decreased dFNC in all states, particularly within cognitive networks such as the default mode, frontoparietal and visual networks vs. healthy females (P < 0.05, FDR corrected).Our results observed the alterations of connectivity strength only in male patients and time variability in female ones, suggesting that sex effects may play an important role in the functional impairment and reorganization of RRMS.